Properties and Characteristics of a Bacteriocin from Serratia marcescens - Foulds, John D. (1969)
A strain of Serratia marcescens was found to produce a bacteriocin that inhibits the growth of certain Escherichia coli strains. This inhibition was bacteriocidal rather than bacteriostatic and was not caused by a bacteriophage. Whereas the bacteriocin was inactive on the 7 Serratia strains tested, it killed 11 of the 20 E. coli strains tested for sensitivity. A relationship of the bacteriocin to a possible colicin cannot as yet be excluded, although E. coli mutants resistant to 1 or 2 of 15 different colicins remained sensitive to the bacteriocin. The bacteriocidal effect by the bacteriocin could be interrupted in a substantial fraction of the treated cell population by the addition of trypsin. The synthesis of the bacteriocin was inducible by ultraviolet light or by starvation for thymidine. Both procedures led to a similar increase in maximum bacteriocin titer relative to noninduced cultures.